RANCANG BANGUN RANGKA SHEET METAL ROLL BENDING MACHINE - Syafwan, Elvathna; Alfarizi, M.; Ramdani, Rizki; Saleh, Agus (Jurnal TEDC; Vol 18 No 1 (2024): JURNAL TEDC, 2024)
The machine frame is an important element that cannot be separated in a machine design and manufacture. The frame has a function as a foundation and support that supports a machine. There are still many workshops that use the manual method for the steel bending process. The process of making the bending roll machine frame is carried out through several stages such as data collection, preparation of frame tools and materials, frame manufacturing process, frame testing. And by conducting testing using Autodesk Inventor software, and manual calculations, the results of making a bending roll machine frame are said to be safe to use.